Clinical outcome comparison of laparoscopic radical antegrade modular pancreatosplenectomy vs. laparoscopic distal pancreatosplenectomy for left-sided pancreatic ductal adenocarcinoma surgical resection - Niu, Nan; He, Yuhui; Mou, Yiping; Meng, Sijia; Xu, Peng; Zhou, Yucheng; Jin, Weiwei; Lu, Chao; Xu, Yunyun; Zhu, Qicong; Xia, Tao (Frontiers in Surgery, 2022)
Background: Laparoscopic radical antegrade modular pancreatosplenectomy (LRAMPS) is a validated surgical treatment for patients with left-sided pancreatic ductal adenocarcinoma (PDAC). Additionally, laparoscopic distal pancreatectomy (LDPS) has purported benefits. However, there is limited analysis comparing the results between LRAMPS and LDPS. Thus, this study aimed to compare the short-term and long-term outcomes of patients who underwent LRAMPS and LDPS for PDAC treatment. Methods: Patients with left-sided PDAC that underwent LRAMPS or LDPS during 2015-2021 were retrospectively identified. Demographic and clinicopathologic data were collected. Disease-free survival (DFS) and overall survival (OS) probabilities were obtained. Results: The number of lymph nodes retrieved was significantly greater in the LRAMPS group than in the LDPS group. Several clinicopathological factors, including CA19-9 levels greater than 37 U/ml, positive lymph nodes, moderate to poor tumor differentiation, and peripancreas fat invasion, were associated with DFS. Moderate with poor tumor differentiation was associated with poor DFS (HR 0.568; 95% CI 0.373-0.921; P=0.021). Levels of CA19-9 greater than 37 U/ml, CEA levels greater than 5 ug/ml, larger tumor size, positive lymph nodes, moderate with poor tumor differentiation, peripancreas fat invasion, and adjuvant chemotherapy were all associated with OS. LRAMPS nearly improved OS but did not reach statistical significance. Serum carcinoembryonic antigen (CEA) levels greater than 5 ug/ml (HR 1.693; 95% CI 1.200-1.132, P=0.001), positive lymph nodes (HR 2.410; 95% CI 1.453-3.995; P=0.001), were independently associated with poor OS. Treatment with adjuvant chemotherapy was associated with improved OS (HR 0.491; 95% CI 0.248–0.708; P=0.001). Conclusions: The LRAMPS procedure achieved comparable results to standard LDPS in terms of postoperative outcomes. Treatment with chemotherapy is important for the prognosis of patients with left-sided pancreatic cancer.